Determinan Ketepatan Waktu Pelaporan Keuangan Perusahaan Go Public Sektor Properti dan Real Estate di Indonesia - Diviariesty, Kadek; Asri, Ida Ayu Trisna Yudi; Dewinta, Ida Ayu Rosa; Ekayani, Ni Nengah Seri (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
The phenomenon of late submission of financial reports is the basis for this research, and there are several cases of late submission of financial reports announced by the IDX related to issuers who neglected to submit their financial reports. This study aims to investigate Profitability, Public Ownership, Company Size, and Company Age that influence the timeliness of financial reporting of property and real estate sector. The research is of a quantitative nature, utilizing secondary data from the financial reports of companies obtained from the website Indonesia Stock Exchange (IDX). The population of the study consists of 78 companies, with a sample of 67 companies selected using purposive sampling method, resulting in 201 data samples. Data analysis technique in this study is Logistic Regression analysis. Overall, this study confirms that profitability, public ownership, company size, and company age play crucial roles in ensuring the timeliness of financial reporting, while audit opinion does not show a significant impact on timeliness of financial reporting.